2007
DOI: 10.1103/physrevb.76.184508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and magnetic field on the thickness dependence of the critical current density ofYBa2Cu3O7x

Abstract: In order to shed light on the puzzling thickness ͑t͒ dependence of the critical current density ͑J c ͒ in YBa 2 Cu 3 O 7−x ͑YBCO͒ films at 77 K and self-field, we have investigated J c -t behavior as a function of temperature ͑T͒ and applied magnetic field ͑H͒ in the thickness range that is within the modified Larkin length L c . It has been found that the J c -t behavior can be well described by the collective pinning ͑CP͒ model as monotonically decreasing J c ϳ t −1/2 when thermal assisted flux motion ͑TAFM͒… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This seems to agree with the observed higher threshold value of H for the TAFM to be effective in the high T group. As we reported earlier on YBCO films without BZO doping, 6 a reversed J c − t trend is observed when TAFM dominates, which is the case for both low T and high T group at H Ͼ 0.5 T. 6 The observation of negligible thickness dependence of J c in low H fields in BZO doped YBCO films supports the previous argument that the collective pinning mechanism is responsible for the observed J c − t in standard YBCO films. This observation is also consistent with our previous report on reduced thickness dependence of J c in YBCO/NTP samples.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…This seems to agree with the observed higher threshold value of H for the TAFM to be effective in the high T group. As we reported earlier on YBCO films without BZO doping, 6 a reversed J c − t trend is observed when TAFM dominates, which is the case for both low T and high T group at H Ͼ 0.5 T. 6 The observation of negligible thickness dependence of J c in low H fields in BZO doped YBCO films supports the previous argument that the collective pinning mechanism is responsible for the observed J c − t in standard YBCO films. This observation is also consistent with our previous report on reduced thickness dependence of J c in YBCO/NTP samples.…”
Section: Resultssupporting
confidence: 84%
“…Interestingly, the lower J c values of YBCO/BZO films in SF and lower H fields can not be attributed completely to the T c difference and moreover, high J c s are observed for thicker YBCO/BZO films. In addition, unlike for the standard films, on which temperature has a pronounced effect on J c − t through TAFM, 6 the J c of YBCO/BZO shows nearly no thickness dependence in a large range of temperatures ranging from = 0.11 to = 0.86. This suggests that the TAFM is greatly suppressed in the SF by the strong correlated pinning from aligned BZO nanorods along the c-axis.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The thickness effect refers to the phenomenon where the J c of a superconducting thin film depends strongly on its thickness, resulting in a crossover thickness that separates the thickness-dependent and thickness-independent regimes. This effect is predicted by the collective pinning theory, 33,53,54 which proposes that each vortex is collectively pinned by point defects when subjected to a magnetic field. At small thicknesses, the short segments of the vortex are independently pinned parallel to the field, resulting in high J c values.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…The thickness dependence of J c for our IBS CCs is quite different from that in cuprate superconductors. It has been found that the J c - t behavior in cuprate superconductors can be addressed by collective pinning theory, by which the J c reduction with increasing thickness can be well described as J c ∼ t −1/2 , followed by a crossover thickness t c , over which J c becomes almost thickness independent ( Wang and Wu, 2007 ; Tran et al., 2013 ; Gurevich, 2007 ). It is interesting to note that the thinnest films with the lowest T c showed the highest J c up to 5 T for H//c and 9 T for H//ab .…”
Section: Resultsmentioning
confidence: 99%